2012
DOI: 10.1111/hel.12016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clarithromycin‐Resistant Helicobacter pylori by Stool PCR in Children: A Comprehensive Review of Literature

Abstract: Detection of clarithromycin-resistant H. pylori by stool PCR for children are reliable, rapid, noninvasive methods that are worthy of further clinical promotion. However, more evaluations of stool PCR in detection of clarithromycin-resistant H. pylori in children need to be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 65 publications
1
29
0
1
Order By: Relevance
“…However, in USA, CLA resistance was found in only 8.6% [36, 37]. Some researchers have reported that a higher prevalence of resistance to both CLA and FLQ was detected in samples from stool compared to biopsy, and they suggested that this could be related to the existence of mixed infections with both resistant and susceptible strains [38]. Whereas this could partly explain our findings, it also could imply that when patients harbouring mixed infections receive antibiotics, the resistant strains naturally become selected for making the drug resistant problem even worse.…”
Section: Discussionmentioning
confidence: 99%
“…However, in USA, CLA resistance was found in only 8.6% [36, 37]. Some researchers have reported that a higher prevalence of resistance to both CLA and FLQ was detected in samples from stool compared to biopsy, and they suggested that this could be related to the existence of mixed infections with both resistant and susceptible strains [38]. Whereas this could partly explain our findings, it also could imply that when patients harbouring mixed infections receive antibiotics, the resistant strains naturally become selected for making the drug resistant problem even worse.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of polymerase inhibitors in the biological sample and possible contamination during sample collection present obstacles to overcome. Currently, the clinical use of PCR-based testing is limited by the expensive costs, but the high diagnostic performance in the pre-and post-treatment setting, with additional option of identifying clarithromycinresistant strains, renders it an excellent future diagnostic method, particularly in children [32].…”
Section: Research Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Another criticism of our study relates to the clinical relevance of in vitro testing; however, with the exception of MET, the concern that susceptibility results do not predict treatment efficacy is largely unfounded (33)(34)(35)(36). Furthermore, the future of susceptibility testing may be noninvasive stool PCR-based testing, which will obviate direct culture (37). A future study might be enhanced by including resistance data for additional antibiotics which are sometimes used to treat refractory H. pylori, such as furazolidone, rifabutin, and nitazoxanide (38)(39)(40).…”
Section: Discussionmentioning
confidence: 95%